Deformation mechanism of WC single crystals under nanoindentation: Effects of surface defects and orientation on pop-in and hysteresis. (August 2022) - Zhang, H.; De Luca, F.; Wang, H.; Mingard, K.; Gee, M.
Abstract: Nanoindentation was carried out on pure tungsten carbide (WC) on the basal (0001) and prismatic (1010) planes, using Berkovich and spherical indenters, in both single load and multi-load testing. The work focuses on correlating the load-displacement curves, including elastic to plastic deformation, size effect and hysteresis with the deformation behaviour of WC. With different specimen preparation processes, the elastic to plastic deformation started at different threshold loads: This observation was found to be due to the variation in surface dislocation density. Staircase deformation was observed thought to be caused by dislocation motion and the formation of slip bands; sudden displacement discontinuities in the load-displacement response - associated with dislocation loop nucleation - occurred at, or near the theoretical shear strength. Furthermore, discontinuities in load-displacement curves were also used to confirm that hysteresis loops were a result of plastic deformation, as they were absent when the loading was purely elastic. Highlights: Pop-ins occurs during loading and unloading, indicative of stress accumulation. Defects in WC determines the yield strength via dislocation motion or initiation. Critical shear stress for dislocation nucleation close to the theoretical value Lack of activated slip systems and anisotropy caused nanoindentation hysteresis.